A critical search for the learning object across school and out-of-school contexts: A case of entrepreneurship education. Issue 3 (27th May 2021) - Engeström, Ritva; Käyhkö, Leena
ABSTRACT: Background : Recent alternative concepts of school knowledge emphasize knowledge creation via networks of learning around real-world phenomena. We studied entrepreneurship education as an example of new epistemic activity which opens institutional boundaries for active engagement with society in learning. Methods : We used a case-study strategy and a methodology informed by the cultural-historical activity theory for investigating an entrepreneurship course of a middle school. We focused on meaning making in object formation of learning of the groups involved in boundary crossing. Meaning making was studied in a context-sensitive way with an analytic tool designed in the study. Findings : Lacking a knowledge system of a disciplinary school subject, the findings show that entrepreneurship becomes constructed in practice epistemologically as a value-free and politically neutral learning object. In light of these findings we discuss the theoretical link between conceptual learning and learning around real-world phenomena. Contribution : In addition to economic activity, globalization and climate change are also presently forming the social realities of school learners. Our study shows that more theoretical and empirical research on intermediate epistemological practices is needed to avoid a risk that teachers are left on their own to sort out the complex epistemic interrelationships.